The Meaningful Universe: Intersecting Forces in Beaver Indian Cosmology - Mills, Antonia (Culture, 1986)
The Beaver Indians of Northeastern B.C. view the events of their world as the manifestation of forces operating between the various levels of spirit. This fundamental shamanic world view has undergone several waves of Christian influence. The first part of the paper describes the meaningful universe that resulted from the intersection of the ancient shamanic philosophy with the Prophet Dance religion. The second part of the paper describes the recent conversion of some Beaver to Pentecostal Christianity and then compares this world view to the antecedent shamanic, the current Prophet Dance and the White Pentecostal philosophy. It demonstrates that the Beaver Indian “Meaningful Universe” maintains a striking similarity to its past versions.